Assessment of Vedolizumab Disease‐Drug‐Drug Interaction Potential in Patients With Inflammatory Bowel Diseases. Issue 7 (16th December 2020) - Sun, Wan; Lirio, Richard A.; Schneider, Jennifer; Aubrecht, Jiri; Kadali, Harisha; Baratta, Mike; Gulati, Parul; Suri, Ajit; Lin, Tiffany; Vasudevan, Raghavan; Rosario, Maria
Abstract: Disease‐drug‐drug interactions (DDDIs) have been identified in some inflammatory diseases in which elevated proinflammatory cytokines can downregulate the expression of cytochrome P450 (CYP) enzymes, potentially increasing systemic exposure to drugs metabolized by CYPs. Following anti‐inflammatory treatments, CYP expression may return to normal, resulting in reduced drug exposure and diminished clinical efficacy. Vedolizumab has a well‐established positive benefit‐risk profile in patients with ulcerative colitis (UC) or Crohn's disease (CD) and has no known systemic immunosuppressive activity. A stepwise assessment was conducted to evaluate the DDDI potential of vedolizumab to impact exposure to drugs metabolized by CYP3A through cytokine modulation. First, a review of published data revealed that patients with UC or CD have elevated cytokine concentrations relative to healthy subjects; however, these concentrations remained below those reported to impact CYP expression. Exposure to drugs metabolized via CYP3A also appeared comparable between patients and healthy subjects. Second, serum samples from patients with UC or CD who received vedolizumab for 52 weeks were analyzed and compared with healthy subjects. Cytokine concentrations and the 4β‐hydroxycholesterol‐to‐cholesterol ratio, an endogenous CYP3A4 biomarker, were comparable between healthy subjects and patients both before and during vedolizumab treatment. Finally, a medical review of postmarketing DDDI cases related to vedolizumab from the past 6 years was conducted and did not show evidence of any true DDDIs. Our study demonstrated the lack of clinically meaningful effects of disease or vedolizumab treatment on the exposure to drugs metabolized via CYP3A through cytokine modulation in patients with UC or CD.